Physiology and Growth of Douglas-Fir and Redwood Seedlings Planted After Partial Harvesting - Kerhoulas, Lucy; Polda, Wade; Kerhoulas, Nicholas; Berrill, John-Pascal (Frontiers in Forests and Global Change, 2020)
Reforestation following timber harvests and natural disturbances is an essential component of sustainable forest management. As disturbances such as drought-induced mortality and wildland fires spread across many forests of the western U.S., a better understanding of the influences of stand structure on seedling physiology can foster more effective reforestation efforts. Moreover, as climate throughout the West is projected to become hotter and drier, it is important to investigate regeneration under xeric conditions, particularly for species restricted to mesic habitats. To study the influences of stand structure and climate on regeneration success, we monitored physiology (water potential [Ψ] and stomatal conductance [gs]), growth (change in basal diameter and biomass accumulation), and mortality rate of planted Douglas-fir (Pseudotsuga menziesii) and coast redwood (Sequoia sempervirens) seedlings for two growing seasons after partial harvesting in inland northern California. Compared to seedlings in the no-cut and moderate-retention treatments, seedlings in the gap (100% cut) treatment had the highest Ψ and gs, greatest growth, and lowest mortality. We also found that compared to Douglas-fir, redwood had higher Ψ and gs, greater growth, and lower mortality. Overall, our study indicates that low-retention silvicultural treatments can minimize water stress and maximize gas exchange, growth, and survival in regenerating seedlings. Our results also demonstrate that redwood, a species generally restricted to mesic coastal habitats, can successfully establish in xeric inland sites when planted after partial harvesting, even during drought conditions.